2017
DOI: 10.1051/medsci/20173306020
|View full text |Cite
|
Sign up to set email alerts
|

Une nouvelle cible thérapeutique dans le traitement de la spasticité après une lésion de la moelle épinière : la calpaïne

Abstract: > À la suite d'un traumatisme de la moelle épi-nière, la plupart des patients développent une exagération du tonus musculaire, appelée spasticité, qui aboutit souvent à une incapacité motrice. Dans cette revue, nous résumerons les principaux mécanismes physiopathologiques de la spasticité qui découlent d'une lésion médul-laire, puis décrirons l'apport de nos récents travaux identifiant une protéase, la calpaïne, comme le promoteur de ces mécanismes physiopathologiques. Cette découverte ouvre de nouvelles piste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Excessive calpain activity degrades proteins important for neural function ( 32 ), such as KCC2 in the hippocampus and layer IV of the cerebral cortex after MIUH at E18 ( 34 ) or in the spinal network after SCI ( 35 ). Indeed, recent studies have shown the deleterious contribution of excess calpain activity to cleave KCC2, which becomes inactive and thus contribute to the excitation/inhibition imbalance toward hyperexcitability ( 36 ) and to upregulate the persistent sodium current in motoneurons ( 37 ), thus leading to the development of hyperreflexia and spasticity, as shown after SCI ( 37 , 38 ). Post-mortem cerebral samples from human preterm infants with WMI showed a loss of KCC2 expression ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive calpain activity degrades proteins important for neural function ( 32 ), such as KCC2 in the hippocampus and layer IV of the cerebral cortex after MIUH at E18 ( 34 ) or in the spinal network after SCI ( 35 ). Indeed, recent studies have shown the deleterious contribution of excess calpain activity to cleave KCC2, which becomes inactive and thus contribute to the excitation/inhibition imbalance toward hyperexcitability ( 36 ) and to upregulate the persistent sodium current in motoneurons ( 37 ), thus leading to the development of hyperreflexia and spasticity, as shown after SCI ( 37 , 38 ). Post-mortem cerebral samples from human preterm infants with WMI showed a loss of KCC2 expression ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early inflammation appears to be crucial in the pathogenic cascades and to contribute in the primary and secondary brain injuries, as well as in repair or recovery after insult events. Immunomodulatory interventions targeting inflammation seem beneficial in preclinical models and might have translational potentials ( 1 , 5 , 38 ). It appears crucial to develop new strategies to reinstate excitation/inhibition balance within the sensorimotor circuitry as early as possible after the insult and inflammation cascade inception.…”
Section: Discussionmentioning
confidence: 99%